Soldering Characteristics and Mechanical Properties of Sn-1.0Ag-0.5Cu Solder with Minor Aluminum Addition - Leong, Y.M.; Haseeb, A.S. Md. Abdul (MDPI, 2016)
Driven by the trends towards miniaturization in lead free electronic products, researchers are putting immense efforts to improve the properties and reliabilities of Sn based solders. Recently, much interest has been shown on low silver (Ag) content solder SAC105 (Sn-1.0Ag-0.5Cu) because of economic reasons and improvement of impact resistance as compared to SAC305 (Sn-3.0Ag-0.5Cu. The present work investigates the effect of minor aluminum (Al) addition (0.1–0.5 wt.%) to SAC105 on the interfacial structure between solder and copper substrate during reflow. The addition of minor Al promoted formation of small, equiaxed Cu-Al particle, which are identified as Cu3Al2. Cu3Al2 resided at the near surface/edges of the solder and exhibited higher hardness and modulus. Results show that the minor addition of Al does not alter the morphology of the interfacial intermetallic compounds, but they substantially suppress the growth of the interfacial Cu6Sn5 intermetallic compound (IMC) after reflow. During isothermal aging, minor alloying Al has reduced the thickness of interfacial Cu6Sn5 IMC but has no significant effect on the thickness of Cu3Sn. It is suggested that of atoms of Al exert their influence by hindering the flow of reacting species at the interface.